Relationship between cognitive and sleep–wake variables in asymptomatic offspring of patients with late-onset alzheimer’s disease - Abulafia, Carolina Andrea (2017)
Fil: Abulafia, Carolina. Fundacion De Altos Estudios Univeristarios Fleni. Departamento de Psiquiatría; Argentina